2014
DOI: 10.1155/2014/683681
|View full text |Cite
|
Sign up to set email alerts
|

Sit-to-Stand in People with Stroke: Effect of Lower Limb Constraint-Induced Movement Strategies

Abstract: Background. Weight-bearing asymmetry and impaired balance may contribute to the increased fall risk in people with stroke when rising to stand from sitting. Objective. This study investigated the effect of constraint-induced movement (CIM) strategies on weight-bearing symmetry and balance during sit-to-stand in people with stroke. Methods. A nonrandom convenience sample of fifteen people with stroke performed the sit-to-stand task using three CIM strategies including a solid or compliant (foam) block strategy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The motion induced by the device encourages the wearer to increase the use of their paretic leg. This effect is similar to the idea of Constraint Induced Movement Therapy [15,16]. By slightly destabilizing their nonparetic leg, the user will naturally start to spend more time on their paretic side, which may help to foster those abilities and confidence in using that side of their body.…”
Section: Therapeutic Mechanismsmentioning
confidence: 64%
See 1 more Smart Citation
“…The motion induced by the device encourages the wearer to increase the use of their paretic leg. This effect is similar to the idea of Constraint Induced Movement Therapy [15,16]. By slightly destabilizing their nonparetic leg, the user will naturally start to spend more time on their paretic side, which may help to foster those abilities and confidence in using that side of their body.…”
Section: Therapeutic Mechanismsmentioning
confidence: 64%
“…Unfortunately, results are inconsistent across patient populations with these treatment options, and there are not set devices facilitating these treatments. Some other gait correction methods currently being studied include Constraint Induced Movement Therapy [15,16], body-weight support [17], robotic [18], functional electrical stimulation [19], transcranial magnetic stimulation [20], and full-body gait exoskeletons [21].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Duclos et al 25 reported that in hemiparetic individuals, improving sit-to-stand symmetry by positioning the affected foot behind the non-affected foot did not increase medio- 26 This study found that the asymmetrical group showed a significant increase in static and dynamic balance in comparison to the spontaneous group after repetitive sit-to-stand training. Based on this result, it is clear that training in an asymmetrical position with the paretic foot back increased the medio-lateral stability limit and the anterior-posterior stability limit, which improved balance control.…”
Section: Discussionmentioning
confidence: 73%
“…Meanwhile, the position of the asymmetric feet while standing up from a sitting position improves the static and dynamic postural balance in patients with stroke (17). In addition, the use of the step model, motion limiting strategies, repetition of sitting motion, repetitive task-oriented practice with sensory input changes, exercise on unstable surfaces, and the use of a cane and weight-bearing exercises along with biofeedback have been reported to improve the STS task in this group of patients (18,20,30,32,(35)(36)(37)(38). Interventions or training focusing on the sit-to-stand task improves the time taken to sit-to-stand and the lateral symmetry (weight distribution between the legs) during the sit-to-stand task (6).…”
Section: Discussionmentioning
confidence: 98%
“…Using a seat with a higher height than normal can be a useful exercise for patients who are unable to maintain the paretic foot behind while sitting. Moreover, constraint-induced movement increases weigh bearing of the paretic limb, and with this method, the center of pressure and the center of mass of the body will tend to the paretic limb (20). However, allowing the subjects to adopt the spontaneous strategy or training of the symmetric strategy could result in greater benefits for subjects with higher chronicity and higher functional levels (21).…”
Section: The Feet Position and Its Effect On The Symmetrical Distribumentioning
confidence: 99%